The Subjectivities and Politics of Occupational Risk: Mines, Farms and Auto Factories - Hall, Alan (Routledge, 2020)
The Subjectivities and Politics of Occupational Risk links restructuring in three industries to shifts in risk subjectivities and politics, both within workplaces and within the safety management and regulative spheres, often leading to conflict and changes in law, political discourses and management approaches. The state and corporate governance emphasis on worker participation and worker rights, internal responsibility, and self-regulative technologies are understood as corporate and state efforts to reconstruct control and responsibility for Occupational Health and Safety (OHS) risks within the context of a globalized neoliberal economy. Part 1 presents a conceptual framework for understanding the subjective bases of worker responses to health and safety hazards using Bourdieu’s concept of habitus and the sociology of risk concepts of trust and uncertainty. Part 2 demonstrates the restructuring arguments using three different industry case studies of multiple mines, farms and auto parts plants. The final chapter draws out the implications of the evidence and theory for social change and presents several recommendations for a more worker-centred politics of health and safety.The book will appeal to social scientists interested in health and safety, work, employment relations and labour law, as well as worker advocates and activists. –Publisher's description. Contents: 1. Introduction and Research MethodsPart 1: Risk Subjectivities and Practices2. Identifying Hazards and Judging Risk3. Taking Risks or Taking a Stand: Interests, Power and IdentityPart 2: Case Studies of Health and Safety in Hard Rock Mining, Family Farming and Auto Parts Manufacturing 4. Transforming the Mining Labour Process: Transforming Risk and its Social Construction5. Reconstructing Miner Consent: Management Objectives and Strategies6. The Transformation and Fragmentation of Canadian Agriculture7. Health and Safety in Farming8. The Transformation of Production and Health and Safety in Auto Parts Manufacturing.9. Participation and Control in a Non-Union Auto Parts Firm10. Conclusion and Implications for Change.